Doença granulomatosa crônica autossômica: relato de caso e análise genético-molecular de dois irmãos brasileiros (2004)
ABSTRACT: Objective: To report the case of two siblings with chronic granulomatous disease. Chronic granulomatous disease is a primary immunodeficiency disorder characterized by abnormal microbicidal activity. Mutations in the p47-phox gene (NCF-1) are present in about 30% of the patients with chronic granulomatous disease; this group presents a better prognosis and later onset of recurrent infections as compared with the X-linked variant, present in about 56% of patients. Description: Case 1 is a female presenting repeat infections since age 10, starting with impetigo followed by severe pneumonia six months later. The severity of the lung infection associated with liver abscess and the patient s resistance to treatment prompted laboratory investigation for immunodeficiency. The results of the nitroblue tetrazolium and superoxide release tests were consistent with a diagnosis of chronic granulomatous disease. The parents and siblings were assessed, revealing the presence of granulomatous disease in a brother (Case 2). He also presented repeat infections with impetigo at age 10, followed by pneumonia six months later, however in a non severe form. Single-strand conformational polymorphism analysis detected abnormal electrophoretic mobility of exon 2 of the NCF-1 gene. Sequence DNA analysis revealed a dinucleotide GT deletion in exon 2. Comments: It is important to evaluate the relatives of chronic granulomatous disease patients, even in the absence of typical clinical signs. Defining the mutation and its correlation with phenotype is important to provide appropriate genetic counseling and clinical prognosis.